The Influence of Financial Performance, Dividend Policy, Capital Structure, and Green Accounting on Firm Value - Khuluqi, Khusnul; Sugeng, Andry; Afandi, Agus; Giovani, Alexander (Jurnal Penelitian Ekonomi Dan Akuntansi, 2025)
The aim of this research is to analyze and empirically test the influence of financial performance, dividend policy, capital structure, and green accounting on firm value. This research is a type of quantitative research using secondary data obtained from the Indonesian Stock Exchange and company websites. The population in this study was 44 technology sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period using purposive sampling technique as the sample selection method, resulting in 17 companies that met the sample criteria. The data analysis technique used in this research is panel data regression analysis using Eviews 13. The results of this study reveal that partially the capital structure variable has an influence on firm value, while financial performance, dividend policy, and green accounting have no influence on firm value.